Les lettres médiévales françaises au profit de l’étudiant : observations d’une universitaire polonaise - Anna Gęsicka (Perspectives Médiévales)
The intention of this paper is to share the author’s afterthoughts based on many years of her schooling experience - an academic teacher and medievalist. The developments of the mental attitude of an “average student” of the romance language faculty has been regarded for twenty years and provoke thoughts of the right teaching methods that would not only provide the necessary knowledge but at the same time arouse the students’ interest in French medieval literature. The first part of the paper gives a summary of three Polish scientists on challenges and pitfalls concerning any research of old literature. The second part renders the conclusions on methods that appear to be effective in educational processes.